In silico and in vitro-guided identification of inhibitors of alkylquinolone-dependent quorum sensing in Pseudomonas aeruginosa - Soukarieh, Fadi; Oton, Eduard Vico; Dubern, Jean-Frédéric; Gomes, Janice; Halliday, Nigel; de Pilar Crespo, Maria; Ramírez-Prada, Jonathan; Insuasty, Braulio; Abonia, Rodrigo; Quiroga, Jairo; Heeb, Stephan; Williams, Paul; et al. (MDPI, 2018)
Pseudomonas aeruginosa is a major opportunistic pathogen in cystic fibrosis, wound and nosocomial infections, posing a serious burden to public health, due to its antibiotic resistance. The P. aeruginosa Pseudomonas Quinolone System (pqs) quorum sensing system, driven by the activation of the transcriptional regulator, PqsR (MvfR) by alkylquinolone (AQ) signal molecules, is a key player in the regulation of virulence and a potential target for the development of novel antibacterial agents. In this study, we performed in silico docking analysis, coupled with screening using a P. aeruginosa mCTX::PpqsA-lux chromosomal promoter fusion, to identify a series of new PqsR antagonists. The hit compounds inhibited pyocyanin and alkylquinolone signal molecule production in P. aeruginosa PAO1-L and PA14 strains. The inhibitor Ia, which showed the highest activity in PA14, reduced biofilmformation in PAO1-L and PA14, increasing their sensitivity to tobramycin. Furthermore, the hepatic and plasma stabilities for these compounds were determined in both rat and human in vitro microsomal assays, to gain a further understanding of their therapeutic potential. This work has uncovered a new class of P. aeruginosa PqsR antagonists with potential for hit to lead optimisation in the search for quorum sensing inhibitors for future anti-infective drug discovery programs.